1990
DOI: 10.1002/hlca.19900730508
|View full text |Cite
|
Sign up to set email alerts
|

Eine weitere, diesmal erfolgreiche Suche nach 3′‐Epilutein in Pflanzen

Abstract: The 3'-epilutein, an extremely rare carotenoid, found till now in only one plant, was detected in anthers of flowers of several roses and in those of peonies. Das 3'-Epilutein (1) ist im Pflanzenreich bisher erst in Bliiten von Caltha palustris (Sumpfdotterblume) entdeckt worden [2] [3]. Es wird dort begleitet von 3',0-Didehydrolutein (2) und Lutein (3) [4], was darauf hinweist, dass seine Bildung auf einen Dehydrierungs-und (nicht-stereospezifischen) Reduktionsprozess am allylischen OH-C(3) zuriickzufiihren i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The 3′ hydroxyl group is allylic, unlike in its regioisomer, zeaxanthin (3) (Figure S1). Some stereoisomers can be found in nature, such as 3′-epilutein (2) with an (all-E,3R,3′S,6′R) configuration, which has been isolated from goldfish (Carassius auratus) [9], marsh marigold (Caltha palustris) [10][11][12], and other flowers [13]. Moreover, 3′-epilutein (2) forms from lutein (1) under acid-catalyzed epimerization in processed plants [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3′ hydroxyl group is allylic, unlike in its regioisomer, zeaxanthin (3) (Figure S1). Some stereoisomers can be found in nature, such as 3′-epilutein (2) with an (all-E,3R,3′S,6′R) configuration, which has been isolated from goldfish (Carassius auratus) [9], marsh marigold (Caltha palustris) [10][11][12], and other flowers [13]. Moreover, 3′-epilutein (2) forms from lutein (1) under acid-catalyzed epimerization in processed plants [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The main mono-Z-isomers (9Z, 9′Z, 13Z, and 13′Z) of both lutein (1) and 3′-epilutein (2), as well as a di-Z-isomer (9Z,9′Z) of lutein, were prepared via the thermal and the I2-catalyzed photoisomerization of their solutions [20][21][22]. In 1981, our research group isolated and identified these isomers via open column chromatography on calcium carbonate, and 13 C-NMR studies confirmed the existence of four mono-cis isomers at positions 9, 9′, l3, and 13′, respectively. In 2001, geometrical isomers of lutein (1) and zeaxanthin (3) were separated using hyphenated HPLC-MS and HPLC-NMR systems on a C30 column [23].…”
Section: Introductionmentioning
confidence: 99%
“…The route is commonly based on two reaction steps namely 1) the acid-mediated epimerization of 3′-allyl alcohol by using aqueous solutions of strong mineral acids such as HCl, H 2 SO 4 , HClO 4 , or CF 3 COOH in THF (room temp., 12-72 h) [11,[24][25][26][27][28] to obtain a mixture of lutein/3′-epilutein in a diastereomeric ratio of 1:1 to 1:5 and 2) a base-mediated isomerization reaction (ε-rearrangement) of the corresponding lutein/3′-epilutein mixtures to yield meso/trans-zeaxanthin by use of polar protic solvents at high temperatures (Figure 1B). [27,[29][30][31] It is worth mentioning that 3′-epilutein (4) has been discovered in a few plant species, such as lichens of the Bialowieza forest, [32] Caltha palustris flowers, [33] peonies and anthers of roses, [34] and marigold extracts, [35] as well as in the tissues of animals, predominantly fish species. [22] Recently, the influence of 3′-epilutein (4) on the increase in macular pigment optical density (MPOD) was demonstrated in patients with age-related macular degeneration (AMD).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In contrast with lutein, from plants, 3 0 -epilutein was only isolated from the petals of Caltha palustris 7 and it was detected in anthers of flowers of several roses and in those of peonies. 8 Determination of the biological activity of different carotenoid stereoisomers requires careful qualitative and quantitative analysis of the functional foods during cooking processes. There is a perception that carotenoids are destroyed by the heat processes involved in cooking vegetables.…”
mentioning
confidence: 99%